Midnight horizon - e uthor.9 (2022)
Confronting the anarchistic marauders known as the Nihil, the Jedi Knights and their Padawans are put to the test, but soon discover that nothing is what it seems.
After a series of losses, the Republic seems to have the villainous Nihil marauders on the run. Jedi Masters Cohmac Vitus and Kantam Sy are sent to the world of Corellia, in the Galactic Core, to investigate a suspected Nihil attack. There, Padawans Reath Silas and Ram Jomaram encounter security specialist Crash, whose friend was one of the victims of the attack. What they uncover on Corellia turns out to be part of a great plan-- one that could lead the Jedi to their most stunning defeat yet. -- adapted from jacket
Keywords: Jedi (Fictitious characters) -- Juvenile fiction; Life on other planets -- Juvenile fiction; Space warfare -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Jedi (Fictitious characters) -- Fiction; Life on other planets -- Fiction; Space warfare -- Fiction; Star Wars fiction; Science fiction; Action and adventure fiction; Science fiction; Novels